Probability and random processes for electrical and computer engineers - Therrien, Charles W. (CRC Press, 2012)
"Updated and written in a clear, concise style, this second edition offers an introduction to probability and random variables, making the subject relevant and interesting for students in electrical and computer engineering. It features applications and examples that are also useful to anyone involved in other branches of engineering or physical sciences. Chapters focus on the probability model, random variables and transformations, inequalities and limit theorems, random processes, and basic combinatorics. The author reinforces presentation of these and other topics using MATLAB computer projects that are available on the CRC Press website"--